DESCRIPTION OF SANDY AREAS OF FERGANA VALLEY - Jobborov Azamjon Mashrabovich; Meliyev Muzaffar Saidakbarovich (Web of Journals Publishing, 2024)
This article provides a general description of the sandy areas located in the southwestern part of the Fergana Valley. Geomorphological features, climatic conditions and biological diversity of sandy areas were studied. Also, ecological problems arising as a result of anthropogenic effects are considered. The results of the research show that it is necessary to take the necessary measures in the sustainable management of sandy areas, to strengthen environmental monitoring and to fight against soil erosion. Maintaining the natural balance of these areas is ecologically and economically important
Keywords: Ferghana Valley, sandy areas, geomorphology, ecological balance, anthropogenic impact, soil erosion, ecological monitoring, sustainable management.